The Paradox of Latina Religious Leadership in the Catholic Church - Torres, T. author. aut Link
XII, 202 p. 8 illus.
Keywords: Religion and social action is both empowering and limiting for women. This study shows the Guadalupanas' awareness of themselves as agents for change and their difficulties in understanding and maintaining their limited gendered roles within church and community.